Analisis Faktor-faktor yang Mempengaruhi Pengelolaan Pamsimas di Desa Banglas Barat Kecamatan Tebing Tinggi Kabupaten Kepulauan Meranti - Sukarman; Baskoro Wicaksono (Nakhoda: Jurnal Ilmu Pemerintahan, 2017)
This research is motivated target PAMSIMAS village election in the village of Banglas Barat years 2014-2016 in accordance with the decree of the minister of public works decree No. 79 / Kpts / DC / 2013 on stipulation district / city target PAMSIMAS. Implementers program PAMSIMAS at the district level conducted by the planning office and the department of public health office of human settlements POKJA AMPL is incorporated in regency Kepulauan Meranti, while implementers at the village level is done by the village government, KKM, SATLAK, BPSPAMS and community facilitator team. The research directs the factors that influence the management of the PAMSIMAS program. Research to know the factors that influence the management of PAMSIMAS program.The type used in this research is descriptive research with qualitative research approach. Type of research data is primary data and secondary data. Data collection techniques in this study is documentation and interviews. Technical analysis of the data used is descriptive qualitative data analysis. The result of the research shows that there are several factors that influence the management of PAMSIMAS in terms of the content of the benefit factor policy and the degree of change to be achieved which is still a constraint, while in terms of policy environment the role of Village Government and Local Government is still minimal in doing support in terms of material as well development of PAMSIMAS facilities that have not been able to reach all PAMSIMAS beneficiaries.